Biofilm-Forming Capacity in Biogenic Amine-Producing Bacteria Isolated from Dairy Products - Diaz, Maria; Ladero, Victor; del Rio, Beatriz; Redruello, Begoña; Fernández, María; Martin, M. Cruz; Alvarez, Miguel A. (Frontiers in Microbiology, 2016)
Biofilms on the surface of food industry equipment are reservoirs of potentially food-contaminating bacteria - both spoilage and pathogenic. However, the capacity of biogenic amine (BA)-producers to form biofilms has remained largely unexamined. BAs are low molecular weight, biologically active compounds that in food can reach concentrations high enough to be a toxicological hazard. Fermented foods, especially some types of cheese, accumulate the highest BA concentrations of all. The present work examines the biofilm-forming capacity of 56 BA-producing strains belonging to three genera and 10 species (12 Enterococcus faecalis, 6 Enterococcus faecium, 6 Enterococcus durans, 1 Enterococcus hirae, 12 Lactococcus lactis, 7 Lactobacillus vaginalis, 2 Lactobacillus curvatus, 2 Lactobacillus brevis, 1 Lactobacillus reuteri and 7 Lactobacillus parabuchneri), all isolated from dairy products. Strains of all the tested species - except for L. vaginalis - were able to produce biofilms on polystyrene and adhered to stainless steel. However, the biomass produced in biofilms was strain-dependent. These results suggest that biofilms may provide a route via which fermented foods can become contaminated by BA-producing microorganisms.